Hybrid Warfare and Deniability as Understood by the Military - Håkan Gunneriusson (Polish Political Science Yearbook, 2019)
Russia and China are terraforming the maritime environment as part of their warfare. In both cases the actions are illegal and the performance is offensive to its actual nature. In the case of China, the practice is construction of artificial islands in the South Chinese Sea and in the case of Russia it is about the infamous bridge built over the Kerch strait, Ukraine. Neither Russia nor China expects an armed conflict with the West in the near future. That is a reasonable assumption, which is weaponized at the political-strategically level. The attack of this weaponized situation is that the trust in the West. Primarily the EU (European Union) and NATO (North Atlantic Treaty Organization), is eroded for every day which these countries challenges the international system which the western democracies say that they present and defend. China and Russia offer their authoritarian systems as a replacement and there are a lot of pseudo-democratic or even out-right authoritarian regimes on the sideline watching this challenge unfold. The article highlights the difference for the NATO-countries in logic of practice when it comes to the political social field on one hand and the military political field on the other hand. The article uses material from a previously unpublished survey made on NATO-officers then attending courses at NATO Defense College (NDC).